2012
DOI: 10.1021/jp3050324
|View full text |Cite
|
Sign up to set email alerts
|

Nuclease Activity and Cytotoxicity Enhancement of the DNA Intercalators via Graphene Oxide

Abstract: The enhancement of DNA affinity of small molecules usually ensures their high nuclease activities, and may also open a new scope of their applications in biology and medicine. In this work, we demonstrate that the nuclease activity and cytotoxicity of the small DNA intercalators can be dramatically enhanced by single atomic-layered graphene oxide (GO) sheets. Through π–π stacking interaction mainly between GO and the aromatic ligands of intercalators, the conjugates of GO and a small intercalator could be form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Noticeably, the activity enhancement is critically dependent on the ratio between GQD and DOX. This observation is analogous to the behavior of the GO/chemical nuclease conjugates26, suggesting that GQDs possibly work together with DOX molecules.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Noticeably, the activity enhancement is critically dependent on the ratio between GQD and DOX. This observation is analogous to the behavior of the GO/chemical nuclease conjugates26, suggesting that GQDs possibly work together with DOX molecules.…”
Section: Resultssupporting
confidence: 68%
“…The DNA plasmid was incubated with different concentration of DOX and GQD at 37°C, quenched by addition of the loading buffer (0.05% bromophenol blue, 1% SDS, and 50% glycerol). The mixture was then subjected to electrophoresis on a 0.5% agarose gel containing ethidum bromide (0.5 μg mL −1 ) in TBE buffer at 90 V for approximately 1 h2526.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports indicate that GO interacts with single‐stranded and double‐stranded DNA ex vivo and with DNA intercalators . However, cellular studies have shown no accumulation of GO in the cell nucleus or mutagenesis .…”
Section: Resultsmentioning
confidence: 99%
“…In that case, GQDs were employed as drug carriers; the effect of GQDs themselves to the cell nuclei was ignored; and whether GQDs also are involved in the interaction with the DNA, which might reinforce the function of DOX, is unclear at the molecular level. In fact, we previously found that graphene oxide could intercalate to DNA molecules in vitro, and recently we also discovered that GQDs could stabilize DNA with i‐motif structure in vitro, and more essentially, GQDs could promote the formation of i‐motif structure under alkaline or physiological conditions . Notably, C‐rich DNA sequences that can form i‐motif structure are often found in the oncogenes .…”
Section: Introductionmentioning
confidence: 99%